2018
DOI: 10.1021/acs.orglett.8b02753
|View full text |Cite
|
Sign up to set email alerts
|

Bunte Salt CH2FSSO3Na: An Efficient and Odorless Reagent for Monofluoromethylthiolation

Abstract: A practical and efficient monofluoromethylthiolation that employs the typical Bunte salt, sodium S-(fluoromethyl) sulfurothioate, as the sulfur source is described. This reagent reacts readily with a variety of aryl amines and aryl thiols. The high tolerance of functional groups demonstrates the potential of this reaction. In addition, this method is suitable for the late-stage monofluoromethylthiolation of complex bioactive molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 56 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…The monofluoromethylthio moiety (SCH 2 F) widely exists in a variety of biologically active compounds (Supplementary Fig. 1 ) 44 , 45 . Previous reports to achieve aldehydic C–H monofluoromethylthiolation relied on the use of stoichiometric oxidants such as 2,2′-azodi(2-methylbutyronitrile) (AMBN) 46 or PhI(O 2 CCF 3 ) 2 /NaN 3 17 .…”
Section: Resultsmentioning
confidence: 99%
“…The monofluoromethylthio moiety (SCH 2 F) widely exists in a variety of biologically active compounds (Supplementary Fig. 1 ) 44 , 45 . Previous reports to achieve aldehydic C–H monofluoromethylthiolation relied on the use of stoichiometric oxidants such as 2,2′-azodi(2-methylbutyronitrile) (AMBN) 46 or PhI(O 2 CCF 3 ) 2 /NaN 3 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in 2018 the group of Yi described the synthesis of the Bunte salt FCH2SSO3Na 8 for the installation of the SCH2F residue (Scheme 3. . This motif was introduced onto anilines through the in situ formation of the corresponding diazonium salts [45]. This transformation demonstrated an excellent scope, various functionalities were tolerated and heteroaromatic derivatives were compatible.…”
Section: The Sch2f Motifmentioning
confidence: 99%
“…Moreover, disubstituted aniline and trisubstituted aniline could also be converted to the corresponding products in moderate yields ( 2 i – 2 k ). In our previous work of monofluoromethylthiolation, 1‐monofluoromethyl‐thio‐3,4,5‐trimethoxybenzene could only be detected by GC‐MS and decomposed quickly, while its monofluoromethylseleno analogue 2 k was stable, no decomposition was observed even after more than three months of storage on a shelf at ambient temperature. It indicated that SeCFH 2 ‐containing compounds were more stable than their SCFH 2 analogues.…”
Section: Figurementioning
confidence: 99%